DEVELOPMENT OF INDUSTRY-BASED PjBL LEARNING METHODS - Tri Murhanjati Sholihah; Prihastuti Ekawatiningsih; Minta Harsana; Ngabdul Munif; Rizki Hidayati; Yuni Triastuti (Journal of Research in Social Science and Humanities, 2025)
This study aims to develop an industry-based Project-Based Learning (PjBL) method that integrates real industrial practices into the learning process to improve students’ technical competencies, problem-solving skills, and workplace readiness. The development process adopts a research and development (RD) approach consisting of needs analysis, model design, expert validation, limited trials, and large-scale implementation. The industry-based PjBL model emphasizes collaborative project work, industrial mentoring, authentic tasks, and assessment aligned with industry standards. Research findings show that the developed model is feasible, practical, and effective in enhancing learning engagement, digital literacy, and job-related competencies. Students demonstrate improved communication, teamwork, and the ability to solve real-world industrial problems. This model is expected to strengthen the link and match between educational institutions and industry, creating a more relevant and responsive learning ecosystem for vocational and higher education.